IoT and Cloud System Implementation Based on FIWARE for Smart Home Application - Angga Pradipta Kurnia Putra; Zaky Oktavianto Wahyu; Reksa Prastama Putra (ISAS, 2026)
Third-party smart home platforms raise significant security and privacy concerns due to their centralized hosting models. This study develops a decentralized, easily deployable smart home platform using the FIWARE IoT framework that enables users to host systems on private servers. The platform integrates FIWARE Generic Enablers (Orion, Keyrock, Wilma, IoT Agent) with custom web, mobile, and desktop applications, containerized using Docker Compose. Hardware nodes (NodeMCU ESP8266 with DHT11 sensors and relay modules) operate without a central gateway. The system successfully achieved full CRUD functionality across client applications, with automated Arduino sketch compilation and upload. However, performance testing revealed critical latency anomalies, with the Orion Context Broker exhibiting rare but severe response delays up to 10 seconds. While the platform successfully addresses privacy concerns and simplifies deployment, FIWARE's resource consumption and occasional latency spikes present optimization challenges requiring future work.